POSISI DAN KEKUATAN HUKUM SERTIFIKAT JAMINAN FIDUSIA DALAM PRAKTIK PERDAGANGAN PEMBIAYAAN KONSUMEN BERDASARKAN UNDANG-UNDANG NOMOR 42 TAHUN 1999 TENTANG JAMINAN FIDUSIA - Muhammad Hendra (jurnal.unprimdn.ac.id, 2021)
At present the trading practice of consumer finance companies is one of the existing financing institutions and is recognized by the Government of the Republic of Indonesia through Presidential Decree No. 61 of 1988 dated December 20, 1988 concerning Financing Institutions or better known as the December 1988 Policy Package which was further confirmed by the issuance of the Decree of the Minister of Finance No. 1251 / KMK.013 / 1988 Concerning finance companies, has been transformed into a large trade that is ravaging, living and growing rapidly in the midst of society. Meanwhile, on the other hand, the increasing number of trade transactions through consumer financing companies indirectly creates various kinds of legal problems that accompany it. Therefore, Law Number 42 of 1999 concerning fiduciary security exists as a legal umbrella for the birth of a guarantee institution that protects rights and interests as well as provides legal certainty for parties in consumer financing trade transactions.